Interpolated Altitudinal Species Richness in Arghakhachi District of Nepal - Nepali, Babu Ram; Skartveit, John; Baniya, Chitra Bahadur (Journal of Institute of Science and Technology, 2020)
The magnitude of climatic variables over space and time determines the altitudinal variation of species richness. The present study has been carried out to determine the vascular plant species richness patterns along with altitude in the Arghakhanchi district (27° 45' to 28º 06' N and 80° 45' to 83° 23' E), West Nepal. The published literature related to the altitudinal distribution of vascular plant species in Arghakhanchi district was collected and enlisted a total of 597 species. The altitudinal range of the Arghakhanchi district was 200-2300 meters above sea level (masl) which was divided equally into 21 bands of 100 m each. The total number of vascular species that occurred at each 100 m contour elevation was considered as the species richness. The objective of this study was to find the vascular plant species richness pattern in Arghakhanchi district concerning altitude and climatic variables. The generalized linear model (GLM) was applied to the total species richness against altitude, annual mean temperature (AMT), and mean annual rainfall (MAR). Total vascular species richness showed a statistically significant unimodal pattern with a maximum richness of 471 species at 1300 masl (r2= 0.91; p < 0.001). Likewise, gymnosperm, dicot, monocot, and pteridophyte species richness showed a highly significant unimodal altitudinal richness pattern. Altitudes of modeled maximum species richness were found varied according to the taxa.